2017
DOI: 10.1126/science.aan6733
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch repair deficiency predicts response of solid tumors to PD-1 blockade

Abstract: The genomes of cancers deficient in mismatch repair (MMR) contain exceptionally high numbers of somatic mutations. In a proof-of-concept study, we previously showed that colorectal cancers with MMR deficiency were sensitive to immune checkpoint blockade with anti-PD-1 antibodies. We have expanded this study to now evaluate efficacy of PD-1 blockade in patients with advanced MMR-deficient cancers across 12 different tumor types. Objective radiographic responses were observed in 53% of patients and complete resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

95
4,502
9
57

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 5,261 publications
(4,663 citation statements)
references
References 36 publications
95
4,502
9
57
Order By: Relevance
“…PD-L1 expression have frequently been observed in MSI tumors with strong correlation to high levels of CD3 and CD8 positive cells. 12,14,2830 In line with our results, PD-L1 expression are more frequently observed on immune cells at the invasive margin and rarely observed on tumor cells. 11,14,31 PD-L1 has been detected as a soluble ligand and may potentially be secreted by MMR deficient tumor cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…PD-L1 expression have frequently been observed in MSI tumors with strong correlation to high levels of CD3 and CD8 positive cells. 12,14,2830 In line with our results, PD-L1 expression are more frequently observed on immune cells at the invasive margin and rarely observed on tumor cells. 11,14,31 PD-L1 has been detected as a soluble ligand and may potentially be secreted by MMR deficient tumor cells.…”
Section: Discussionsupporting
confidence: 91%
“…The first studies have shown high degree of response in advanced-stage tumors, though patients with Lynch syndrome may have a somewhat lower response rate than patients with somatic MMR defects. 10-12 …”
Section: Introductionmentioning
confidence: 99%
“…However, PD-1 and PD-L1 blocking antibodies were proven unsuccessful in CRC, with the exception of MMR-deficient CRC. 23-25 , 27 , 28 The first aim of this study was to investigate whether the composition of the immune infiltrates and the intra-tumoral expression levels of inhibitory molecules in CRC metastases in the liver environment differ from those in primary CRC tumors and metastases outside the liver, which would suggest potential differences in sensitivity to checkpoint inhibitors among CRC tumors at different anatomical locations. The second objective was to determine whether targeting of inhibitory checkpoint pathways by antagonistic antibodies can enhance the functionality and anti-tumor responses of tumor-infiltrating T cells in LM-CRC.…”
Section: Discussionmentioning
confidence: 99%
“…22-25 In contrast, CRC patients hardly respond to PD-1 and PD-L1 blocking antibodies, 23-26 except for the minority of patients who are with mismatch repair (MMR)-deficient CRC. 27 , 28 A defective MMR enzyme system occurs in 10%-20% of CRC tumors and results in microsatellite instability, which is used as a molecular marker of MMR-deficiency. 29 It has been hypothesized that the observed difference in responsiveness to PD-1/PD-L1 blockade between MMR-deficient and MMR-proficient CRC is related to the higher numbers of somatic mutations in MMR-deficient tumors, due to the reduced ability to repair DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, objective responses were observed in only 53% of patients with deficient mismatch repair (dMMR) solid tumors and in 31% of distant metastatic CRC patients with high microsatellite instability (MSI-H). 6-8 The best candidates that benefit from immune checkpoint therapy are still unclear.…”
Section: Introductionmentioning
confidence: 99%